Experimental Observation and Computer Simulation of Al/Sn Substitution in p-Type Aluminum Nitride-Doped Tin Oxide Thin Film - Cheng-Yi, L. (2016)
In this study, the Al3+-Sn4+ substitution reaction in the AlN-doped SnO2 thin films is confirmed by photoluminescence and X-ray photoelectron spectrum analysis. Also, both Al3+-Sn4+ and N3--O2- substitution reactions are verified by computational simulation, Vienna ab initio simulation package (VASP). The computational simulation shows that both Al and N impurity dopants generate an unoccupied band at the upper valence band maximum, which produces holes within the upper valence band region. Both Al3+-Sn4+ and N3--O2- substitution reactions contribute to the p-type conversion of AlN-doped SnO2 thin films. Annealing AlN-doped SnO2 (Al content is 14.65%) thin films at high-temperature (larger than 350 C), N outgassing would occur and cause the p-type conduction of the annealed AlN-doped SnO2 thin films back to n-type conduction. Yet, in this work, we found that the Al3+-Sn4+ substitution reaction in the high Al-doping concentration of Al-doped and AlN-doped SnO2 (the Al content is between 29% and 33.2%) thin films would be activated considerably, as they are annealed at a temperature over 500 C. With a higher Al-doping concentration (Al concentration is 33.2%) in the Al-doped SnO2 thin films, we found that the critical annealing temperature for the n-to-p conduction transition decreases to 500 C. The Al dopants in the AlN-doped SnO2 thin films annealed at high annealing temperature not only stabilize the N3--O2- substitution reactions but also produce hole carriers by the Al3+-Sn4+ substitution reactions. The Al3+-Sn4+ substitution makes the AlN-doped SnO2 retain the p-type conduction in the high-temperature annealing. © 2016 American Chemical Society.